Pembentukan Negara Islam di Indonesia antara Idealitas dan Realitas (Kajian Fiqh Tata Negara) - Muzakki, Ahmad Muzakki (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Until now there are groups that continue to fight for the upholding of khilâfah islâmiyyah in Indonesia. They believe that khilâfah is the only solution for all problems of the people. And there are groups who believe that the khilâfah is difficult to realize now because every Islamic country in the world has a different system and form of government.According to this second group the state is only the will and the benefit of the people is the main goal.There are three important issues discussed in this article through the fiqh approach to state administration. First, the principles of Islamic governance from the perspective of theAl-Qur`ân dan Hadith. Second, the realization of the establishment of an Islamic state in modern times.Third, related to the establishment of an Islamic state whether included in part qat`iyyah or ijtihâdiyyah. After going through the discussion, it was concluded that among the principles of Islamic governance were justice, equality, joint discussion, freedom and people's supervision.The establishment of Islamic state in Indonesia and even in the world is still difficult to realize because each country has a different system and form of government.The establishment of an Islamic state is included in the realm of ijtihâdiyyahbecause there are no fixed rules in the Al-Qur`ân dan Hadith related to certain forms and systems of government.Existing rules in the form of universal rules that ultimately estuary are justice and good for the people",